A Moving Target: Changing Priorities in the Energy Policy of the European Union - Somosi, Sarolta; Megyeri, Eszter (International Journal of Energy Economics and Policy, 2022)
The EU’s strategic objective is to improve energy market integration while emphasising the goal of energy sustainability. This study summarises the progress made over the last six decades, particularly focusing on the latest steps, and outlines the present and future challenges of the European energy policy. In doing so, the study addresses the following research questions: Will the EU realise its original aspirations in the field of energy? Is the Energy Union on target to deliver the envisioned breakthrough for the EU? Are the benefits of the Energy Union tangible at the integrated EU level? What new conditions and expectations shape and influence the future of the Energy Union?